MECHANISM OF EFFECTIVE MANAGEMENT OF INDUSTRIAL ENTERPRISES - Sarsenova Akmaral Edilbaevna; Alpysbaeva Ainur Kunanbaevna; Kadyrbay Sabyrzhan Beisenuly (Academic Journal of Physical and Chemical Sciences, 2020)
An important condition for sustainable development of industrial enterprises is the attention to the issues of management efficiency, what implies a change of management methods and necessitates the revision and updating of management tools for the development of industrial enterprises that are appropriate to the market situation and allow taking into account the variety of challenges faced by industry enterprises. These methods and tools can be considered as elements of the industrial business system, which are essentially engines of development of enterprises in the industry. Increasing the contribution of the qualitative component of economic growth through the introduction of effective management tools in the practice of industrial enterprises becomes an urgent task, since the use of modern management tools is currently an important factor in the development of any enterprise. In the current economic conditions, in order to develop approaches to create methodological tools for innovative development, it is necessary to identify effective economic and administrative mechanisms that could accelerate the implementation of structural adjustment of the country’s economy, increase the level of competitiveness and economic efficiency of production in high-tech industries, facilitate import substitution of the electronic component base and individual means of production purchased abroad in all sectors of the economy of the Republic of Kazakhstan. The relevance of the study is determined by the need for a theoretical and conceptual justification for changing attitudes to the formation of effective tools for managing the development of industrial enterprises, focused on the continuous use of organizational transformation opportunities that ensure a balance of interests of business participants and contribute to the sustainable maximization of business value. The article presents review of a conceptual approach to the formation of an integrated efficiency management mechanism, formulated on the basis of a systematic study of the essential properties and methodological principles that define the category "efficiency of the enterprise management system". The task of maximizing the economic result on the basis of balanced management in all interrelated areas of efficiency growth has been formulated. The features that are associated with the identification of effective management tools for industrial enterprises have been examined. The properties of general features of management tools have been highlighted, the main characteristics of enterprise management tools have been formed, and the mechanism of effective enterprise management has been presented.